Multiple gas reservoirs are responsible for the gas emissions along the Marmara fault network. (July 2018) - Ruffine, Livio; Donval, Jean-Pierre; Croguennec, Claire; Burnard, Pete; Lu, Hailong; Germain, Yoan; Legoix, Ludovic N.; Bignon, Laurent; Çağatay, M. Namık; Marty, Bernard; Madre, David; Pitel-Roudaut, Mathilde; et al.
Abstract: On continental margins, upward migration of fluids from various sources and various subsurface accumulations, through the sedimentary column to the seafloor, leads to the development of cold seeps where chemical compounds are discharged into the water column. MarsiteCruise was undertaken in November 2014 to investigate the dynamics of cold seeps characterized by vigorous gas emissions in the Sea of Marmara (SoM). A previous paper published by Bourry et al. (2009) presented the gas geochemistry of three seeps sampled along three different segments in the SoM. Their findings showed that the seeps were sourced by three different reservoirs. In this paper, seventeen seeps were investigated to determine the gas sources, unravel reservoir contributions, and estimate their level of mixing. The molecular and stable isotope compositions of the gas compounds were determined to establish the empirical diagrams that usually allow to delineate source domains. The results provide insights into the complexities of source mixing within the sedimentary column of the SoM before emission of the gases into the water column. The seep gases originate from deep thermogenic or microbial hydrocarbon sources, or from a CO2 -rich source. Microbial sources producing methane from primary methanogenesis have been identified in the Tekirdağ and the Çınarcık basins. In addition, six different thermogenic reservoirs or six different pathways of migration are responsible for the supply of gas to the seeps on the highs and in the western basin. Five of them are undergoing biodegradation followed by secondary methanogenesis, thereby providing additional sources of microbial methane to the seeps. Overall, the gases emitted by the seventeen seeps consist of variable mixtures of different components from two or three sources.